Topical chemotherapy for ocular surface squamous neoplasia: current status. Issue 5 (23rd September 2009) - Sepulveda, Ricardo; Pe'er, Jacob; Midena, Edoardo; Seregard, Stefan; Dua, Harminder S; Singh, Arun D
Abstract : Although there are no randomised trials directly comparing topical chemotherapeutic agents mitomycin-C, 5-fluorouracil, and interferon-α2b, published studies indicate equal efficacy of these agents for treatment of non-invasive ocular surface squamous neoplasia (80%–88%). 5-Fluorouracil may be preferred, given low incidence of serious side effects and low cost to the patient.